The Impact of Destination Image, Promotions, and Ticket Prices on Visiting Decisions Evidence From Situ Rawa Gede, Bekasi City - Risa Awalia Setiawati; Kristiana Widiawati (Universitas Indonesia Membangun (Inaba), 2026)
The tourism industry continues to grow due to increasing recreational needs and the rapid dissemination of information about tourist destinations. This study examines tourism distribution inequality in West Java and tourist visit dynamics at Situ Rawa Gede, Bekasi City. It aims to analyze the influence of destination image, promotion, and ticket prices on visiting decisions. A quantitative approach was employed using data from 117 respondents selected through non-probability and purposive sampling. Data were analyzed using SPSS 29.0. The results indicate that destination image has a positive and significant effect on visiting decisions (Sig. = 0.006; t = 2.776), while promotion also has a positive and significant effect (Sig. < 0.001; t = 4.796). In contrast, ticket price does not significantly affect visiting decisions (Sig. = 0.713; t = 0.369). Simultaneously, destination image, promotion, and ticket price significantly influence visiting decisions, explaining 45.7% of the variance. This research confirms that visiting decisions are shaped by the integration of multiple marketing elements rather than a single factor. The study implies that tourism managers should strengthen destination image and deliver effective promotional content to increase tourist visits and support sustainable tourism development.